Informed consent: a socio-legal study - Rathor, Mohammad Yousuf; Abdul Rani, Mohammed Fauzi; Mohamad Shah, Azarisman Shah; Akter, Sheikh Farid Uddin (Malaysian Medical Association, 2011)
Introduction: Informed consent [IC] is a recognized socio-legal obligation for the medical profession. The doctrine of IC involves the law, which aims to ensure the lawfulness of health assistance and tends to reflect the concept of autonomy of the person requiring and requesting medical and/or surgical treatment. Recent changes in the health care delivery system and the complex sociological settings, in which it is practiced, have resulted in an increase in judicial activity and medical negligence lawsuits for physicians. While IC is a well-established practice, it often fails to meet its stated purpose. In the common law, the standard of medical care to disclose risks has been laid down by the Bolam test- a familiar concept to most physicians, but it has been challenged recently in many jurisdictions. This paper aims to discuss some important judgments in cases of alleged medical negligence so as to familiarize doctors regarding their socio-legal obligations. We also propose to discuss some factors that influence the quality of IC in clinical practice. Methods: Literature review. Results: The law of medical consent has been undergoing changes in recent years. Case law appears to be evolving towards a more patient centered standard of disclosure. Patient’s expectations are higher and they are aware of the power of exercising their rights. Failure to obtain IC is one of the common allegations in medical malpractice suits. Conclusion: The medical professionals need to change their mindset and avoid claims of negligence by providing information that is “reasonable” in the eyes of the court. Key Words: Informed consent, medical negligence, Medical ethics, Investigation, Bolam test